STRATEGI PERANG SEMESTA MELALUI IMPLEMENTASI SILA PANCASILA PERSATUAN INDONESIA GUNA MENCEGAH PAHAM RADIKALISME DI DAERAH ISTIMEWA YOGYAKARTA - Tonny Sumarno; Lukman Yudho Prakoso (Strategi Perang Semesta, 2021)
Yogyakarta Special Region is one of the historical provinces in Indonesia. Since the Indonesian nation fought for independence until the struggle to defend independence, Yogyakarta and its people have provided the best work for the Indonesian people. The high culture which is the legacy of the ancestors is well preserved. The Special Region of Yogyakarta is also known for its polite attitude towards anyone who comes. As a student city, Yogyakarta has produced many leaders. So that it becomes a special attraction for young people in Indonesia and abroad to study in Yogyakarta, this makes the city of Yogyakarta a "Center of Gravity" of science and culture. The demonstration of Papuan students as a form of solidarity due to the news of racism surrounding Papuan students in Surabaya is one indicator of the emergence of the seeds of disintegration of the nation's children, which the Yogyakarta Special Region Government must immediately address. The purpose of this research is to analyze how the Universal War Strategy through the implementation of the Principles of Pancasila of Indonesian Unity can be applied in preventing the spread of radicalism in Yogyakarta, which threatens the disintegration of the nation's children, and how to re-instill the noble values of Pancasila, especially the precepts of the Indonesian Unity, for the students who are studying in Yogyakarta. The method used in this research is to use a qualitative descriptive analysis method with data sources from secondary data which are strengthened by several theories. From the results of research and data processing, it is found that there is a significant influence, the spread of radicalism against disintegration, so it can be concluded that the implementation of the Universal War Strategy through the implementation of the Principles of Pancasila of the Indonesian Unity can be applied through the "Defend the State" and "Re-ground Pancasila" program, in order to prevent and counteract the spread of radicalism in the Special Region of Yogyakarta.